Utilization of a partially-deoiled chia flour to improve the nutritional and antioxidant properties of wheat pasta. (March 2018) - Aranibar, Carolina; Pigni, Natalia B.; Martinez, Marcela; Aguirre, Alicia; Ribotta, Pablo; Wunderlin, Daniel; Borneo, Rafael
Abstract: Pasta is a popular staple food. Today, there is a trend to consume less processed foods. Products fortification with certain properties, such as antioxidant potential and dietary fiber, represents an added value. Chia is an ancient grain, that contains exceptional proportions of polyunsaturated fatty acids (ω-3/ω-6). After oil extraction, a residue, termed partially-deoiled chia flour (PDCF), high in protein content, dietary fiber, and phenolic compounds, remains as a by-product. The main goal of this work was to evaluate the nutritional and technological quality of pasta supplemented with PDCF at different proportions (2.5%, 5% and 10%). Parameters such as texture, color, microstructure, protein and fiber content, polyphenol content and antioxidant activity (FRAP and DPPH) were analyzed. A sensory evaluation has been also performed. Our results demonstrate that the addition of PDCF improves the antioxidant capacity with respect to a non-supplemented pasta (0% PDCF). The acceptance of pasta by semi-trained judges was also good. As a concluding remark, the study confirms the feasibility to introduce this food product, and also lead us to consider a profitable application of a by-product of the chia oil extraction process. Highlights: A feasible use of a by-product from chia oil extraction (PDCF) is proposed. PDCF is rich in protein, dietary fiber and phenolic compounds. It can be used as an ingredient to improve the nutritional quality of wheat pasta. Supplemented pasta showed better antioxidant capacity. The technological properties and the acceptance by consumers were evaluated.